Citrus in Albania: virological problems and efforts for the establishment of a certification programme - Stamo B. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
Little is known on the presence and distribution of virus and virus-like diseases of citrus in Albania. Concave gum, psorosis A, cristacortis and impietratura were detected only by visual inspection. A project, in collaboration with IAM-B and the University of Bari, has been outlined for the establishment of the citrus improvement programme.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)